Preparation of activated carbon and its adsorption of naphthalene in liquid paraffin oil - Xiong, He; Xiao, Yang; Yan, Zhiguo (Colloid and interface science communications, 2021)
Liquid paraffin oil is harmful to organisms as it contains noxious substances such as aromatic hydrocarbons. Since liquid paraffin oil is difficult to be decomposed in organisms, liquid paraffin oil will eventually reach the human body through the food chain. Besides, the presence of aromatic hydrocarbons in liquid paraffin oil also debases the downstream products. Therefore, it is of great practical value to remove aromatic hydrocarbons in liquid paraffin oil. In this study, pinecone-based activated carbon was prepared to adsorb naphthalene, which is a typical aromatic hydrocarbon in liquid paraffin oil. The prepared adsorbents were characterized by Scanning Electron Microscopy (SEM), N2 adsorption-desorption isotherms, X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). N2 adsorption-desorption isotherms manifested that the specific surface area (SSA) amplified with the KOH/precursor proportion. Although the highest SSA (1191 m2/g) was achieve in the adsorbent with an impregnation rate of 1:4 (KOH/precursor), the sample with an impregnation rate of 1:2 showed the largest adsorption capacity (435 mg/g) of naphthalene. This indicated that the SSA was not directly proportional to the adsorption capacity of naphthalene and the existence of mesoporous was also favorable for adsorption. The adsorption kinetic parameters were fitted with the pseudo-first-order, pseudo-second-order, and intra-particle diffusion models. The adsorption isotherms were fitted by Langmuir and Freundlich models. Finally, the KOH activation mechanism was also discussed. [Display omitted] •Pinecone-based activated carbons are obtained for naphthalene adsorption in liquid paraffin oils.•The activated carbon morphology, specific surface area and adsorption conditions are investigated.•The adsorption capacity of naphthalene increases after KOH activation.•The adsorption capacity of PPC-2 is larger than of PPC-4.